A Novel Approach to Integrated Science Teaching and Learning in a Selected Ghanaian Junior High School - Geoffrey Yao Klutse (Foxton Books, 2021)
The study was about a novel approach to Integrated Science teaching and learning in a selected Ghanaian junior high school. In this study, the approach to teaching and learning Integrated Science has been made entirely new and meaningful in the sense that the four learning behaviours (acquisition of knowledge, comprehension, application of knowledge and experimental skills) which constitute profile dimensions were incorporated into the objective-stating, lesson-delivery and assessment of lessons. The researcher made use of profile dimensions in preparing lesson plans, taught students with the new strategy and assessed the impact of the new approach on students in terms of teaching and learning of science. The students were highly interested in answering low order question. About 80% of the questions were high order questions which were poorly answered. They actually showed very little interest in answering high order questions. However, as the weeks went by and the approach to teaching the new strategy was improved, students' interests were aroused and sustained leading to students demonstrating high ability to answer high order questions conveniently. By the end of the study, the students were able to set up and conduct experiments, observe the outcome and draw their own conclusions. The students could classify items based on their characteristics and discuss issues (like balanced diet) and outline the effect of malnutrition in animals. Students' scientific drawings were neater and clearer with less woolen lines. The implication of the finding is that, with these learning behaviours and skills, students could do analytical thinking and have the capacity to apply their knowledge to problems and issues.